Dimensional Engineering of a Graded 3D–2D Halide Perovskite Interface Enables Ultrahigh Voc Enhanced Stability in the p‐i‐n Photovoltaics. Issue 20 (14th July 2017) - Bai, Yang; Xiao, Shuang; Hu, Chen; Zhang, Teng; Meng, Xiangyue; Lin, He; Yang, Yinglong; Yang, Shihe
Abstract: 2D halide perovskite materials have shown great advantages in terms of stability when applied in a photovoltaic device. However, the impediment of charge transport within the layered structure drags down the device performance. Here for the first time, a 3D–2D (MAPbI3 ‐PEA2 Pb2 I4 ) graded perovskite interface is demonstrated with synergistic advantages. In addition to the significantly improved ambient stability, this graded combination modifies the interface energy level in such a way that reduces interface charge recombination, leading to an ultrahigh V oc at 1.17 V, a record for NiO‐based p‐i‐n photovoltaic devices. Moreover, benefiting from the graded structure induced continuously upshifts energy level, the photovoltaic device attains a high J sc of 21.80 mA cm −2 and a high fill factor of 0.78, resulting in an overall power conversion efficiency (PCE) of 19.89%. More importantly, it is showed that such a graded interface structure also suppresses ion migration in the device, accounting for its significantly enhanced thermal stability. Abstract : A designer cross‐dimensional perovskite–perovskite (3D–2D) interface upshifts the energy level toward the surface, pronouncedly reduces the charge recombination in perovskite photovoltaics, leading to a record high V OC at 1.17 V. Strongly enhanced ambient and thermal stability is also demonstrated.